try thisOriginally Posted by Hayabusa
eq1 x=3y-2
eq2 2x+4y=16
eq2 - 2(eq1)
..2x+4y=16
-2(x=3y-2)
-----------
0+4y=16-3y+2
or
4y=18-3y
7y=18
y=18/7, now plug in y to either equation to find x
Well, the answer has to be 'no' as you can see by trying the values you've obtained in the original equations. For example, if x=6 and y=0 then 3y-2=-2 and this isn't equal to x, so the first equation isn't satisfied. 2x+4y=12 and so the second isn't satisfied either, but your answer would have had to be wrong even if only one of the two had failed.Originally Posted by Hayabusa
Since you're told to use substitution I think you were being asked to use x=3y-2 in the second equation, so that 2(3y-2)+4y=16 giving 10y-4=16, 10y=20, y=2 and then x=4.